Techno-economic performance of an advanced process for synergistic removal of NO/SO2/CO2 via H2O2 pre-oxidation coupled with ammonia scrubbing - Jiaxing Du; Qingqing Liang; Yifan Wang; Hui Xu; Linlin Xu; Yan Liang; Guangying Wang; Lei Bei; Chuanwei Li; Zewei Zhang; Lushi Sun (Fuel, 2027)

The impact of energy structure on sectoral carbon emissions: Evidence from China - Lei Bei; Chaolong Duan; Yongkui Du; Chao Wu; Wentao Li; Hanping Mao; Wu Yang; Ben Wang; Linlin Xu; Ruisi Wang; Xiao Liu; Lushi Sun; et al. (Energy and Climate Change, 2026)

Interactions of Micro/Nanoplastics and Antibiotics: Research Trends, Toxicological Effects, and Environmental Risks - Junyi Du; Jia Du; Linlin Qiu; Qingwei Zhou; Meiqing Jin; Jianjun Chen; Weihong Wu (Water, Air, & Soil Pollution, 2026)

IGF1-IGF1R signaling in tumor-associated macrophages regulates extracellular matrix organization in BRAF inhibitor-targeted melanoma - Ya Luo; Linlin Liu; Xing Zhou; Jiao Yang; Min Tang; Wei Feng; Chunlan Du; Xiaobo Liu; Liu Yang; Fei Liu; Liqun Zhang (Molecular and Cellular Biochemistry, 2026)

Aurantio-Obtusin Attenuates Aβ-Induced Cognitive Impairment and Synaptic Dysfunction by Suppressing Neuroinflammation in Mice - Xueying Feng; Wei Yu; Song Guo; Yanyan Ji; Junhua Li; Ling Wang; Guolu Zhong; Shiyi Li; Linlin Niu; Danxin Zhu; Kan Zhou; Yehong Du (Journal of Neuroimmune Pharmacology, 2026)

Retraction notice to “Study on the effect of SDBS and SDS on deep coal seam water injection” [Sci. Total Environ. 856 (2023) 158930] - Lianman Xu; Yajing Li; Linlin Du; Fengshuo Yang; Runjie Zhang; Hao Wei; Gang Wang; Zhe Hao (Science of The Total Environment, 2026)

Co-combustion of municipal solid waste and antibiotic fermentation residue: Gaseous pollutant emissions and ash slagging characteristics - Changhong Huang; Yuhang Du; Lei Bei; Jiaxing Du; Wu Yang; Ben Wang; Linlin Xu; Lushi Sun (Fuel, 2026)

Dimethyl fumarate ameliorates quinolinic acid-induced ageing and neurodegeneration in Caenorhabditis elegans - Yi Sun; Ke Zhou; Jiaorong Cui; Haoxuan Ding; Iqra Shareef; Liuliang Du; Zhen Shi; Linlin Fu; Fenfen Sun; Zuobin Zhu; Wei Pan (Biogerontology, 2026)

GAC-YOLO: A Pomegranate Disease Rapid Detection Method with Multi-Scale Feature Enhancement for an Orchard Inspection Robot - Shenghui Fu; Yongchang Deng; Shuangxi Liu; Rongwei Li; Yuefeng Du; Linlin Sun; Hongjian Zhang; Tao Xu; Wen Zhang (Applied Fruit Science, 2026)

Effects of the foliar application of selenite at different growth stages on selenium transformation, silage quality and the metabolome of tiger nut (Cyperus esculentus L.) - Kexin Wang; Ting Gong; Xinge Du; Wei Liu; Ruize Sun; Chenghao Che; Yilin Zou; Shengnan Sun; Linlin Mei; Guofu Hu (Food Chemistry, 2026)

Pharmacovigilance insights into drug-induced hypercalcemia: evidence from the U.S. FDA Adverse Event Reporting System (FAERS) database - Wensheng Liu; Linlin Wang; Xue Song; Xuan Ye; Yunlan Ding; Jiyong Liu; Qiong Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Flood susceptibility prediction in the Indo-China Peninsula using 21 years of inundation occurrence data and machine learning - Gangya Huang; Alex Hay-Man Ng; Qianqian Zhou; Qinggaozi Zhu; Zheyuan Du; Linlin Ge (Journal of Hydrology, 2026)

Insights into the mechanism of nutty aroma formation by Staphylococcus saprophyticus in fermented sausages - Jikun He; Youqin Duan; Shuting Yang; Fidel Toldrá; Jiong Zheng; Muying Du; Linlin Wang; Nodali Ndraha; Shuyao Wang; Juan Chen (International Journal of Food Microbiology, 2026)

Advances in the understanding of spatiotemporal distribution and hazard assessment of volcanic tsunamis - Kan Zhang; Linlin Li; Peng Du; Tingting Fan; Weitao Wang; Peizhen Zhang (Science China Earth Sciences, 2026)

Zonal asymmetry of recent heat content change in Antarctic Intermediate Water - Xubin Ni; Ling Du; Linlin Fan; Huangyuan Shi (Journal of Oceanology and Limnology, 2026)

Paleolandslides, paleoshorelines and lacustrine sediment deformation structures in the midstream Tashkurgan River, Chinese Pamir and implications on regional seismic risk - Liao Liye; Zeng Qingli; Du Linlin; Du Changhong; Chen Xuan; Shang Yanjun; Zhou Yuanze (Bulletin of Engineering Geology and the Environment, 2026)

Spatio-temporal pattern and driving mechanism of the coupling coordination of human settlements systems - Xueming Li; Meishuo Du; Linlin Feng; Shenzhen Tian; Jun Yang (Journal of Geographical Sciences, 2026)

Endophytic fungi-mediated drought tolerance in spring wheat under no-tillage with straw cover on the Loess Plateau, China - Changliang Du; Lingling Li; Junhong Xie; Khuram Shehzad Khan; Linlin Wang; Zhuzhu Luo; Lingzhi Li; Zechariah Effah; Muhammad Zahid Mumtaz (Soil and Tillage Research, 2026)

Adsorption mechanism of hydrogen bromide and 2-bromophenol on CuO, Cu2O, α-Fe2O3, and NiO catalysts: A density functional theory study - Lushi Sun; Jiaxing Du; Tao Chen; Gan Wan; Linlin Xu; Li Lin (Journal of Environmental Chemical Engineering, 2026)

Juvenile-Onset Cerebrotendinous Xanthomatosis with Novel Compound Heterozygous CYP27A1 Mutations: Case Series and Literature Review - Kefang Du; Chunrong Wang; Linlin Wan; Zhao Chen; Hongyu Yuan; Qian Jiang; Xiao Dong; Daji Chen; Riwei Ouyang; Xiafei Long; Xiaokang Wu; Xinying Xiao; et al. (The Cerebellum, 2026)

Widespread vegetation damage in Asian Interior due to the 2022 extreme drought - Yu Luo; Linlin Gao; Xiyue Fu; Linhan Si; Xinyue Li; Na Du; Yiyun Yuan; Xiang Zhang; Yang Deng (Environmental Research, 2026)

Study on slow pyrolysis mechanism of non-metallic fractions in waste printed circuit boards using TG-FTIR-MS analysis - Lushi Sun; Gan Wan; Tao Chen; Jiaxing Du; Linlin Xu; Haitao Liu (Journal of Environmental Management, 2025)

The Impact of Microplastics on the Dissemination, Persistence, and Ecotoxicological Effects of Antibiotic Resistance Genes in Terrestrial Ecosystems - Jia Du; Tingting Chen; Luxi Niu; Lanxue Zhi; Linlin Qiu; Qingwei Zhou; Meiqing Jin; Weihong Wu (Water, Air, & Soil Pollution, 2025)

ViruSeg: Harnessing the Power of Large Language-Image Model for Enhanced Virus Image Segmentation - Shengxiang Wang; Xiangzheng Fu; Zhenya Du; Xinxin Liu; Qiaochu Mai; Linlin Zhuo; Boqia Xie; Quan Zou (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Microplastics as vectors for environmental contaminants in the food chain: Assessing the combined toxicological effects and bioavailability - Jia Du; Linlin Qiu; Qingwei Zhou; Meiqing Jin; Weihong Wu (Toxicology Letters, 2025)

Earlywood blue intensity of Picea purpurea reveals June minimum temperature variability in Eastern Tibetan Plateau since 1671CE - Na Du; Shuhua Qiao; Baolong Ma; Xinyue Li; Linhan Si; Linlin Gao; Yang Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

Biochar-induced strong microbial carbon limitation prompts organic carbon sequestration and plant growth in antibiotic-contaminated soil - Linlin Qiu; Tim J. Daniell; Muhammad Nafees; Yihao Chen; Shuyu Zhou; Weihong Wu; Jia Du; Qingwei Zhou; Meiqing Jin; Weiying Ji; Jiaying Ge; Hongyan Guo (Plant and Soil, 2025)

Sources, temporal-spatial characteristics, exposure assessment and children health risk of phthalate esters (PAEs) in household dust in China from 2000 to 2023: a review and pool analysis - Wenying Zhang; Xiaotong Zhang; Xiaomin Xie; Tingting Liu; Fengjing Song; Chengyu Chen; Chao Wang; Linlin Jiang; Hang Du; Lin Fan; Xu Han; Yiming Sun; et al. (Environmental Pollution, 2025)

Monitoring of Larch Caterpillar (Dendrolimus superans) Infestation Dynamics Using Time-series Sentinel Images in Changbai Mountains National Nature Reserve, Northeast China - Linlin Wu; Mingchang Wang; Jiatao Du; Jingzheng Zhao; Fengyan Wang (Chinese Geographical Science, 2025)

Label-Free Direct Detection of 4MU by Plasmon Enhanced Fluorescence Sensing Based on Ag@SiO2 NPs - Liqi Wang; Xin Lv; Ziheng Song; Linlin Tian; Xinyue Du; Dong Zhang; Qingru Wang (Journal of Fluorescence, 2025)

Mechanisms for sulfadiazine effective mitigation in biochar-amended soil: From antibiotic resistance to soil microbial community composition and function - Linlin Qiu; Luxi Niu; Muhammad Nafees; Shuyu Zhou; Weihong Wu; Jia Du; Qingwei Zhou; Meiqing Jin; Hongyan Guo (Journal of Environmental Management, 2025)

Mercury migration characteristics and the re-emission inhibition in seawater flue gas desulfurization system - Chuanwei Li; Gan Wan; Linlin Xu; Jiaxing Du; Lushi Sun; Li Lin (Journal of Environmental Chemical Engineering, 2025)

Licorice water extract improves constipation by repairing the intestinal barrier and regulating the gut microbiota: A potential alternative treatment strategy - Mingwei Sun; Meng Zhao; Linlin Du; Jieying Hou; Juane Dong; Bin Zhang (Food Bioscience, 2025)

Nitrogen-rich carbon nitride activated peroxymonosulfate for the efficient photodegradation of 2, 4-dichlorophenol: Performance and mechanism insight - Tianyu Zhou; Siyi Wang; Meng Tai; Juan Du; Dongshu Sun; Guangbo Che; Linlin Liu; Chunhong Ma; Bo Hu (Environmental Research, 2025)

Polysaccharides from traditional Chinese medicine and their nano-formulated delivery systems for cancer immunotherapy - Linlin Sun; Yuting Liu; Qihui Sun; Guimei Wang; Baoxiang Du; Bodong Liu; Tian Gao; Pan Zhao; Yong Yang; Rong Rong (Carbohydrate Polymers, 2025)

Combined toxicity of decabromodiphenyl ethane and Pb on earthworms (Eisenia fetida) based on multiple biomarker responses - Meiqing Jin; Yuanchao Sun; Bing Chai; Minghu Wang; Yuping Wu; Weihong Wu; Qingwei Zhou; Linlin Qiu; Jia Du; Li Fu (Journal of Soils and Sediments, 2025)

Inter-trophic networks reveal the central role of methanogens in deposited estuarine soils - Linlin Wang; Xiongfeng Du; Wenli Shen; Songsong Gu; Zhaojing Zhang; Zheng Zhang; Baohua Xie; Guangxuan Han; Ye Deng (Soil Ecology Letters, 2025)

3D semantic segmentation: Cluster-based sampling and proximity hashing for novel class discovery - Jing Du; Linlin Xu; Lingfei Ma; Kyle Gao; John Zelek; Jonathan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

The promotion mechanism of ammonia-based CO2 capture by hydroxyl and amine additives: A molecular dynamics and DFT study - Jiaxing Du; Wu Yang; Linlin Xu; Jiaming Chen; Zijian Song; Ben Wang; Lushi Sun (Fuel, 2025)

The dewatering performance of streptomycin mycelial residue promoted by the Fenton process synergistic with biochar - Lushi Sun; Jiaxing Du; Xingxing Zhou; Gan Wan; Linlin Xu; Li Lin (Journal of Environmental Management, 2025)

Tanshinone IIA@β-cyclodextrin encapsulated with Eucommia ulmoides rubber/acetylated starch film as novel oral delivery system for therapy of orthotopic colon cancer - Rui Zhao; Haoyu Wang; Shuyao Li; Lingling Wang; Xiaopeng Lei; Pai Peng; Linlin Du; Juane Dong (Carbohydrate Polymers, 2025)

The dewatering performance and mechanism of streptomycin mycelial residue based on Fenton oxidation - Linlin Xu; Xingxing Zhou; Jiaxing Du; Gan Wan; Lushi Sun (Process Safety and Environmental Protection, 2025)

Novel NIR-Ⅱ-Activated titanate-supported iridium nanoplatform delivers multimodal antitumor therapy synergistic with PD-1 inhibition in TNBC - Peixin Du; Xian Jiang; Zihan Xu; Linlin Song; Meixu Chen; Yujie Zhao; Jing Yu; Tianyue Xu; Ting Sun; Huang Zhu; Hubing Shi; Jing Jing (Chemical Engineering Journal, 2025)

Bivariate Spatial Autocorrelation Analysis of Keshan Disease and Hair Selenium of Residents in Heilongjiang Province, China - Jiacheng Li; Guijin Li; Cheng Wang; Huixin Sun; Linlin Du; Shuxiu Hao; Qingyu Zeng; Cunqi Lv; Yu Zhang; Xinshu Wang; Zhifeng Xing; Tong Wang (Biological Trace Element Research, 2025)

Spatial Clusters of Low Serum Selenium: the Priorities of Selenium Supplementation to Residents of Keshan Disease Endemic Areas - Qingyu Zeng; Guijin Li; Ruixiang Wang; Cunqi Lv; Shuxiu Hao; Jiacheng Li; Huixin Sun; Linlin Du; Cheng Wang; Yu Zhang; Xinshu Wang; Yuehui Jia; et al. (Biological Trace Element Research, 2025)

Impact and mechanism of polyethylene terephthalate microplastics with different particle sizes on sludge anaerobic digestion - Qing Yang; Jiaxin Li; Linlin Ma; Xue Du (Environmental Pollution, 2025)

Earthquake-induced Submarine Landslides (EQISLs) and a comparison with their Terrestrial Counterparts: Insights from a New Database - Peng Du; Linlin Li; Achim Kopf; Dawei Wang; Kejie Chen; Huabin Shi; Weitao Wang; Xiaoyi Pan; Gui Hu; Peizhen Zhang (Earth-Science Reviews, 2025)

Provincial localization framework for SDGs in China: Enhancing support for sustainable governance - Wen Song; Shisong Cao; Mingyi Du; Linlin Lu; Huadong Guo; Sirui Wang; Yue Liu; Xiaoxuan Li (Applied Geography, 2025)

In situ recurrent Hongshiyan paleolandslides at Ludian, China, and Implications on fault activity and hydro-project risk reduction - Liao Liye; Zeng Qingli; Shi Yongyue; Ma Xuping; Du Linlin; Zhou Jian; Zhang Luqing (Landslides, 2025)

Releasing characteristics and influencing factors analysis of nitrogen-containing gaseous pollutants in wastewater treatment plants with sequencing batch reactor process - Linlin Ma; Yufan Dong; Xue Du; Qing Yang; Kehua Zou (Journal of Environmental Chemical Engineering, 2024)

Estimating global 0.1° scale gridded anthropogenic CO2 emissions using TROPOMI NO2 and a data-driven method - Yucong Zhang; Shanshan Du; Linlin Guan; Xiaoyu Chen; Liping Lei; Liangyun Liu (Science of The Total Environment, 2024)

Tailoring carbon intercalated α,β-FePc heterophase junction to boost electron transfer for 1O2-dominated photo-Fenton reaction - Zhiling Du; Cailiang Yue; Linlin Zhu; Changqing Zhu; Qing Du; Fuqiang Liu (Chemical Engineering Journal, 2024)

Monitoring slope stabilization of a reactivated landslide in the Three Gorges Reservoir Region (China) with multi-source satellite SAR and optical datasets - Jianming Kuang; Linlin Ge; Alex Hay-Man Ng; Stuart R. Clark; Sadra Karimzadeh; Masashi Matsuoka; Zheyuan Du; Qi Zhang (Landslides, 2024)

Exploring biomass addition in methanol production: A life cycle analysis of efficiency and environmental impacts - Linlin Liu; Shenghui Li; Yu Zhuang; Jian Du (Journal of Cleaner Production, 2024)

Rice grain quality traits impacted by rice black-streaked dwarf virus disease - Yue Sun; Jiayuan Zhang; Linlin Du; Chenyang Li; Ying Lan; Tong Zhou; Xin Zhou; Baodong Wei; Feng Lin (Journal of Cereal Science, 2024)

Review on post-combustion CO2 capture by amine blended solvents and aqueous ammonia - Jiaxing Du; Wu Yang; Linlin Xu; Lei Bei; Siyuan Lei; Wei Li; Haitao Liu; Ben Wang; Lushi Sun (Chemical Engineering Journal, 2024)

Simplified mechanical calculation model for an entire jack-up platform system - Linlin He; Yuanshi Xie; Yizhong Du; Yang Liu; Mingwei Liu (Ocean Engineering, 2024)

Analysis of Flow Instability and Mechanical Energy Loss of Fluid Field in Fluid Momentum Wheel - Kedong Zhang; Wenhua Wang; Yihua Liu; Linlin Wang; Yazhen Du; Hongxia Li; Yi Huang (Journal of Marine Science and Engineering, 2024)
A new type of anti-rolling device denoted as a fluid momentum wheel (FMW) is proposed to address the limitations of traditional gyrostabilizers in reducing the roll responses of floating platforms in waves. The proposed device is based on the same gyroscope theorem, which differs from a rigid gyrostabilizer in that the internal fluid generates secondary flow in the cross-section under the combined effects of inertial centrifugal force and a radial pressure gradient, and the streamwise velocity exhibits a non-uniform distribution. These instability phenomena may cause mechanical energy loss in the flow field, which is critical for selecting the driving device and the anti-roll control performance of offshore platforms. In the study, different turbulence models are compared with the results of a Direct Numerical Simulation (DNS) and experiments to ensure the accuracy of the numerical method, and the spatiotemporal distribution characteristics of the flow field in FMW are analyzed. Therein, the SST k-ω model accurately verifies the flow instability phenomenon of the FMW observed in the Particle Image Velocimetry (PIV) experiment. Next, this paper proposes corresponding evaluation parameters to assess the impact of typical parameters on the flow field instability. The results show that the flow instability increases with an increase in the typical parameters of FMWs (such as the pipe diameter, curvature radius, and velocity). Furthermore, the paper discusses the relationship between dimensionless mechanical factors (Reynolds number, curvature ratio) and the spatiotemporal instability of the flow field, revealing the essential effects of the curvature ratio and Reynolds number on the loss coefficient.

2-Methoxyestradiol ameliorates paraquat-induced pulmonary fibrosis by inhibiting the TGF-β1/Smad2/3 signaling pathway - Linlin Hou; Fang Yang; Yan Zhang; Yi Li; Hongyi Yan; Cuicui Meng; Yuqi Du; Huanzhou Zhu; Ding Yuan; Yanxia Gao (Pesticide Biochemistry and Physiology, 2023)

Damping, soft, and thermally conductive composite elastomer via introducing bottlebrush chains - Shipeng Rao; Xiangliang Zeng; Xiaxia Cheng; Jianfeng Fan; Dongyi He; Linlin Ren; Guoping Du; Xiaoliang Zeng (Chemical Engineering Journal, 2023)

Improved biomass burning pollution in Beijing from 2011 to 2018 - Linlin Liang; Zhenyu Du; Guenter Engling; Xuyan Liu; Wanyun Xu; Chang Liu; Yuan Cheng; Dongsheng Ji; Gen Zhang; Junying Sun (Atmospheric Environment, 2023)

A novel framework for combining polarimetric Sentinel-1 InSAR time series in subsidence monitoring - A case study of Sydney - Alex Hay-Man Ng; Ziyue Liu; Zheyuan Du; Hengwei Huang; Hua Wang; Linlin Ge (Remote Sensing of Environment, 2023)

Hair Selenium of Residents in Keshan Disease Endemic and Non-endemic Regions in China - Yuehui Jia; Ruixiang Wang; Guijin Li; Chen Feng; Lei Qi; Yuanyuan Wang; Shengqi Su; Yuanjie Zou; Xu Liu; Yanan Wang; Yiyi Zhang; Linlin Du; et al. (Biological Trace Element Research, 2023)

Spatial distribution patterns across multiple microbial taxonomic groups - Xiongfeng Du; Songsong Gu; Zheng Zhang; Shuzhen Li; Yuqi Zhou; Zhaojing Zhang; Qi Zhang; Linlin Wang; Zhicheng Ju; Chengliang Yan; Tong Li; Danrui Wang; et al. (Environmental Research, 2023)

Combined effects of climatic factors on extreme sea level changes in the Northwest Pacific Ocean - Linlin Fan; Ling Du (Ocean Dynamics, 2023)

A rapid and sensitive single-cell proteomic method based on fast liquid-chromatography separation, retention time prediction and MS1-only acquisition - Wei Fang; Zhuokun Du; Linlin Kong; Bin Fu; Guibin Wang; Yangjun Zhang; Weijie Qin (Analytica Chimica Acta, 2023)

Performance of wetland applied to ecological remediation of abandoned fish ponds: A case study in Gonghu Bay, Tai lake - Linlin Li; Jing Zhang; Shaoyong Lu; Hongbin Lu; Zhichao Du; Bin Bi; Fengmei Cao; Weijing Kong (Chemosphere, 2023)

Efflux pumps activation caused by mercury contamination prompts antibiotic resistance and pathogen's virulence under ambient and elevated CO2 concentration - Linlin Qiu; Yabo Wang; Wenchao Du; Fuxun Ai; Ying Yin; Hongyan Guo (Science of The Total Environment, 2023)

Recent advances of plasmonic elemental Bi based photocatalysts in environmental remediation and energy conversion - Cailiang Yue; Linlin Zhu; Yixing Qiu; Zhiling Du; Jinli Qiu; Fuqiang Liu; Fenghe Wang (Journal of Cleaner Production, 2023)

Correction to: Cl-amidine attenuates lipopolysaccharide-induced inflammation in human gingival fibroblasts via the JNK/MAPK, NF-κB, and Nrf2 signalling pathways - Jianxin Du; Ning Wang; Hui Sun; Linlin Zheng; Xiangqin Qi (Human Cell, 2023)

Multi-scale ocean dynamical processes in the Indo-Pacific Convergence Zone and their climatic and ecological effects - Yan Du; Fan Wang; Tianyu Wang; Weiwei Liu; Linlin Liang; Ying Zhang; Yunfan Chen; Jiaxing Liu; Wei Wu; Kefu Yu; Jing Zhang (Earth-Science Reviews, 2023)

RETRACTED: Study on the effect of SDBS and SDS on deep coal seam water injection - Lianman Xu; Yajing Li; Linlin Du; Fengshuo Yang; Runjie Zhang; Hao Wei; Gang Wang; Zhe Hao (Science of The Total Environment, 2023)

Distinctive roles of land-use efficiency in sustainable development goals: An investigation of trade-offs and synergies in China - Wen Song; Shisong Cao; Mingyi Du; Linlin Lu (Journal of Cleaner Production, 2023)

Golden 2-like transcription factor contributes to the major QTL against rice black-streaked dwarf virus disease - Xuejuan Li; Feng Lin; Chenyang Li; Linlin Du; Zhiyang Liu; Wenjuan Shi; Jianying Lv; Xiaoyan Cao; Ying Lan; Yongjian Fan; Yijun Zhou; Tong Zhou (Theoretical and Applied Genetics, 2022)

Cl-amidine attenuates lipopolysaccharide-induced inflammation in human gingival fibroblasts via the JNK/MAPK, NF-κB, and Nrf2 signalling pathways - Jianxin Du; Ning Wang; Hui Sun; Linlin Zheng; Xiangqin Qi (Human Cell, 2022)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Integrated analysis of miRNA and mRNA transcriptomic reveals antler growth regulatory network - Boyin Jia; Linlin Zhang; Yifan Zhang; Chenxia Ge; Fuhe Yang; Rui Du; Hengxing Ba (Molecular Genetics and Genomics, 2021)

Towards a revised framework of modified time series InSAR for mapping land deformation - Zheyuan Du; Linlin Ge; Alex Hay-Man Ng; Qi Zhang (Journal of Geodesy, 2020)

Gelatin Methacrylate (GelMA)-Based Hydrogels for Cell Transplantation: an Effective Strategy for Tissue Engineering - Shining Xiao; Tengfei Zhao; Jingkai Wang; Chenggui Wang; Jiangnan Du; Liwei Ying; Jiangtao Lin; Caihua Zhang; Wanglu Hu; Linlin Wang; Kan Xu (Stem Cell Reviews and Reports, 2019)

A reverse-transcription loop-mediated isothermal amplification (RT-LAMP) assay for detecting the pathogen of maize rough dwarf disease in China - Linlin Du; Wenjuan Shi; Xuejuan Li; Ying Lan; Feng Sun; Yongjian Fan; Tong Zhou; Yijun Zhou (Australasian Plant Pathology, 2019)

Spatiotemporal variability and trends in the hydrology of the Xiang River basin, China: extreme precipitation and streamflow - Juan Du; Linlin Cheng; Qiang Zhang (Arabian Journal of Geosciences, 2019)

Carbon, nitrogen and phosphorus stocks differ among vegetation patch types in a degraded alpine steppe - Yan Yan; Linlin Tian; Ziyin Du; Scott X. Chang; Yanjiang Cai (Journal of Soils and Sediments, 2019)

Investigation on mining subsidence over Appin–West Cliff Colliery using time-series SAR interferometry - Zheyuan Du; Linlin Ge; Alex Hay-Man Ng; Xiaojing Li (International Journal of Remote Sensing, 2018)

Integrated space geodesy for mapping land deformation over Choushui River Fluvial Plain, Taiwan - Linlin Ge; Alex Hay-Man Ng; Zheyuan Du; Horng-Yue Chen; Xiaojing Li (International Journal of Remote Sensing, 2017)

Applicability of TRMM satellite precipitation in driving hydrological model for identifying flood events: a case study in the Xiangjiang River Basin, China - Yumeng Yang; Juan Du; Linlin Cheng; Wei Xu (Natural Hazards, 2017)

Occurrence of diazepam and its metabolites in wastewater and surface waters in Beijing - Congcong Wang; Linlin Hou; Jing Li; Zeqiong Xu; Tingting Gao; Jun Yang; Huafang Zhang; Xiqing Li; Peng Du (Environmental Science and Pollution Research, 2017)

Selenium Deficiency Influences the Expression of Selenoproteins and Inflammatory Cytokines in Chicken Aorta Vessels - Qiang Du; Haidong Yao; Linlin Yao; Ziwei Zhang; Xingen Lei; Shiwen Xu (Biological Trace Element Research, 2016)

Roles of oxidative stress and endoplasmic reticulum stress in selenium deficiency-induced apoptosis in chicken liver - Linlin Yao; Qiang Du; Haidong Yao; Xi Chen; Ziwei Zhang; Shiwen Xu (BioMetals, 2015)

Alternative splicing and immune response of Crassostrea gigas tumor necrosis factor receptor-associated factor 3 - Baoyu Huang; Linlin Zhang; Yishuai Du; Li Li; Tao Qu; Jie Meng; Guofan Zhang (Molecular Biology Reports, 2014)

Lanthanum chloride impairs spatial learning and memory and downregulates NF-κB signalling pathway in rats - Linlin Zheng; Jinghua Yang; Qiufang Liu; Fei Yu; Shengwen Wu; Cuihong Jin; Xiaobo Lu; Lifeng Zhang; Yanqiu Du; Qi Xi; Yuan Cai (Archives of Toxicology, 2013)

Coseismic Slip from the 6 October 2008, M w6.3 Damxung Earthquake, Tibetan Plateau, Constrained by InSAR Observations - Xuejun Qiao; Shaomin Yang; Ruilin Du; Linlin Ge; Qi Wang (Pure and Applied Geophysics, 2011)